2022
DOI: 10.1167/iovs.63.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Correlates of Outer Retina Remodeling in Intermediate Age-Related Macular Degeneration Using Microperimetry

Abstract: Purpose To assess the effect of drusen morphometric changes and choroidal vascular modifications on retinal sensitivity (RS) evaluated through microperimetry in intermediate age-related macular degeneration (iAMD). Methods A retrospective review of 18 iAMD patients (18 eyes) with a 12-month follow-up was performed. Eye-tracked spectral-domain optical coherence tomography was obtained, with automatic segmentation of the outer retinal layer (ORL) delineating the drusen ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…AMD is a multifactorial and complex disease that includes several possible mechanisms: genetic risk factors encoding for the complement system such as complement factor H, CFHR, C2, C3, CFI and SERPING1, inflammatory, oxidative, lipidic, mitochondrial, and microvascular factors [ 17 , 43 ]. Evidence of CC impairment in AMD emerged from several studies with different approaches, including prolonged choroidal filling on both indocyanine green and fluorescein angiography in early AMD, Doppler flow studies, a proteomic analysis that found the loss of CC protein (CA4 and HLA-A) with the preservation of RPE proteins (CRALBP and RPE 65), histopathological studies, and more recently, with the advancements in multimodal imaging [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Structural Changes In Choroidal Vasculature With Aging and D...mentioning
confidence: 99%
See 1 more Smart Citation
“…AMD is a multifactorial and complex disease that includes several possible mechanisms: genetic risk factors encoding for the complement system such as complement factor H, CFHR, C2, C3, CFI and SERPING1, inflammatory, oxidative, lipidic, mitochondrial, and microvascular factors [ 17 , 43 ]. Evidence of CC impairment in AMD emerged from several studies with different approaches, including prolonged choroidal filling on both indocyanine green and fluorescein angiography in early AMD, Doppler flow studies, a proteomic analysis that found the loss of CC protein (CA4 and HLA-A) with the preservation of RPE proteins (CRALBP and RPE 65), histopathological studies, and more recently, with the advancements in multimodal imaging [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Structural Changes In Choroidal Vasculature With Aging and D...mentioning
confidence: 99%
“…The post-processing method is usually applied on a single subfoveal OCT B-scan with optimal visualization of the choroid–scleral junction. However, a volumetric CVI estimation calculating several consecutive B-scans can also be obtained [ 44 , 112 , 113 , 114 ].…”
Section: Choroidal Imaging and Assessment In Vivomentioning
confidence: 99%
“…One strategy to improve the ability to show change over time could be to individualize the test grid and so gain information in specific regions identified as being at risk of progression, such as areas showing early OCT signs of atrophy. Although time intensive to perform, scotopic microperimetry may be of particular use in iAMD cohorts [ 116 ]. In eyes with earlier stages of AMD, scotopic retinal sensitivity is more decreased than photopic or mesopic sensitivity compared to healthy controls [ 117 , 118 ].…”
Section: Structural Biomarkersmentioning
confidence: 99%
“…In contrast to Sonoda’s method, which selects the choroidal area before binarization, in 2016, Agrawal [ 19 ] modified this method by proceeding with binarization before selecting the choroidal area, and they calculated the ratio of the LA to the total choroidal area and called it CVI. In recent years, more studies have used CVI as an indicator to evaluate the choroid in healthy or diseased eyes [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%